Impact of digital infrastructure construction on the migrants' utilization of basic public health services in China - Haowen Jia (BMC, 2024)
Abstract Background Global digitalization significantly impacts public health by improving healthcare access for marginalized populations. In China, socioeconomic disparities and the Hukou system create significant barriers for the migrant population to access basic public health services (BPHS). This study aimed to assess how digital infrastructure construction (DIC) affects BPHS utilization among China's migrant populations, filling a gap in the literature regarding the relationship between digital advancements and health service accessibility. Methods This research used micro-level data from the 2018 China Migrants Dynamic Survey and incorporated variables aligned with the Broadband China policy to employ a comprehensive empirical strategy. It included baseline regressions, robustness checks through propensity score matching and machine learning techniques, and heterogeneity analysis to explore the differential impacts of DIC based on gender, age, education level, and Hukou status. Results The findings revealed that DIC significantly enhances the likelihood of migrants establishing health records and registering with family doctors, demonstrating quantifiable improvements in health service utilization. Heterogeneity analysis further indicated that the beneficial impacts of DIC were more pronounced among female migrants, those with higher education levels, younger populations, and urban Hukou holders. Conclusions DIC plays a crucial role in bridging the accessibility gap to BPHS for migrant populations in China, contributing to narrowing health disparities and advancing social equity. These results emphasize the significance of digital infrastructure in public health strategies and offer valuable insights for policymakers, healthcare providers, and researchers. Future research should prioritize longitudinal studies on the sustained effects of DIC and tailor digital health initiatives to meet the unique needs of migrant populations, promoting inclusive health policy planning and implementation.